Toxinas A e B do Clostridium difficille induzem a expressão diferencial de receptor de Adenosina em células epiteliais intestinais: papel do receptor A2B - Foschetti, Danielle Abreu (2014)
Clostridium difficile is recognized to be a nosocomial pathogen that causes intense intestinal inflammation, epithelial barrier disruption and diarrhea. Adenosine production is increased under inflammatory situations. The adenosine receptor A2B is the most expressed receptor in the human and mice intestine. We investigated the effect of short- and long-term exposure to TcdA and TcdB in HCT-8 cells and isolated cecum epithelial cells. HCT-8 cells were exposed to TcdA or TcdB (10 ng/ml) for 2, 6 and 24h. We used a murine cecal loop model and murine infection model to evaluate the effects of TcdA and C. difficile infection, respectively. We demonstrated that HCT-8 and isolated intestinal cecum epithelial cells naturally express high levels of A2BR receptors. TcdA or TcdB alters the cell morphology, viability and proliferation pattern and caused gene expression increase of all AR subtypes in HCT-8. In isolated cecum epithelial cells, TcdA significantly (p<0.05) increased volume/length, weight/length, histopathology scores, neutrophil infiltration, as measured by MPO content, and induced an altered gene expression increase of all AR subtypes. PSB603 (10 nM) treatment significantly (p<0.05) reduced TcdA-induced tissue damage. Our findings support the hypothesis that Clostridium difficile toxins affect adenosine receptor expression and this action may be related to their severe inflammatory effect. We concluded that adenosine receptors may play a crucial role in regulating the inflammatory system in intestinal epithelium during C. difficile infection.